PELATIHAN PEMIKIRAN BERBASIS RISIKO MENGGUNAKAN TEKNOLOGI KOMPUTER UNTUK MENINGKATKAN AKUNTABILITAS KANTOR DISTRIK NAVIGASI PALEMBANG - Sitepu, Hans Victor (LPPM Universitas Nusa Mandiri, 2024)
With its strategic role, the Palembang Navigation District Office has made substantial efforts to improve the quality of its services, particularly by conducting initiatives to develop Standard Operating Procedures for the many types of services it offers. One of the main activities in this series of activities is providing training entitled Risk-Based Thinking - Identifying Risk Aspects in Processes that can support Accounting and Management Information Systems. The author explains to the participants using three methods: the Lecture Method, the Question-and-Answer Method, and the Case Study Discussion Method, all of which are conducted face-to-face and divided into five sessions, beginning with the opening session, material presentation session, illustration session, question and answer session, and closing session. It is hoped that by participating in this training activity, participants will gain a better understanding of the concept and application of risk-based thinking, as well as skills in using various types of tools, techniques and computer technology commonly used in risk management, which will be integrated into the process of developing the new service procedures. According to the results of the post-activity interview, the Head of the Palembang Navigation Office was satisfied with the training results and his team's absorption of the content.